2015
DOI: 10.1007/s00345-015-1703-4
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lower urinary tract symptoms (LUTS) and erectile dysfunction (ED): results from a survey in males from Mexico City (MexiLUTS)

Abstract: LUTS and ED may represent one of the largest sources of morbidity in our population, and their association was demonstrated. Awareness on these entities should be raised, and further research is required to determine the higher frequency of LUTS and ED in Hispanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The MexiLUTS study published in 2015 surveyed 1041 males to estimate the frequency of LUTS and erectile dysfunction. 10 Consistent with our results, they found that the most commonly reported symptom was nocturia (72.4%). However, a probabilistic sampling technique was not used and the study was conducted in only one center, which might have threatened the external validity of their results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The MexiLUTS study published in 2015 surveyed 1041 males to estimate the frequency of LUTS and erectile dysfunction. 10 Consistent with our results, they found that the most commonly reported symptom was nocturia (72.4%). However, a probabilistic sampling technique was not used and the study was conducted in only one center, which might have threatened the external validity of their results.…”
Section: Discussionsupporting
confidence: 92%
“…11 These definitions were modified for practical reasons and better patient understanding. LUTS were defined as subjective indicators of disease or change in condition as perceived by the patient, and were classified using the International Prostate Symptom Score (IPSS) as mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The prevalence of individual LUTS (ie, urinary frequency, urgency, nocturia, intermittency, weak stream, straining, and incomplete voiding) were determined as ≥1 point in the IPSS for each symptom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar rate of treatment seeking was reported in the EPIC study, with 38% of patients seeking treatment 21 . Likewise, in the MexiLUTS study, surprisingly few (14.6%) men sought treatment, despite the frequency and bother due to LUTS, and the relatively high education level in this cohort (75% had at least high school education) 22 . There are numerous reasons for such variation in reported rates of treatment seeking in patients with OAB, including study design, cultural stigma and belief that LUTS are a natural occurrence with aging and are not treatable or curable 23 .…”
Section: Discussionmentioning
confidence: 77%
“…To date, there have been few reports on the impact of PVEP on sexual function. Recent reports show that LUTS severity is positively correlated with ED (Gonzalez‐Sanchez et al, ; İrer, Çelikhisar, Çelikhisar, Bozkurt, & Demir, ). Moreover, multivariate analysis showed that LUTS can be considered an age‐independent risk factor for ED (Hallanzy et al, ).…”
Section: Discussionmentioning
confidence: 98%